PEMETAAN KERENTANAN DAN PENYUSUNAN JALUR EVAKUASI BENCANA GEMPABUMI (Studi Kasus Di Dusun Sayangan, Desa Jagalan, Kecamatan Banguntapan, Kabupaten Bantul) - , Westi utami ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Disaster mitigation is an effort made to reduce disaster risks. Understanding of the threat of disasters, vulnerability, community capacity and institutional capacity, as well as the pattern of spatial characteristics of an area is important to ensure disaster management working effectively and holistically. Sayangan Village with its condition of high building-density, high population density of 11.941 population per km2 (Census, 2010), and the narrowness of local road (<1.5 m) with old buildings and walls at the sides of the road, would be a problem when there is an earthquake. Based on these problems, this study aims to (1) mapping and analyze the physical, social, economic and environmental vulnerability in Sayangan Village in response to the earthquake threats, (2) analyze the effect of household capacity towards vulnerability, and (3) develop a method for the development of earthquake evacuation route in Sayangan Village. The assessment of vulnerability (physical, social, economic, and environmental) and of community capacity was conducted through a census among 14 neighborhoods (RT) with the number of 365 households in Sayangan Village. Data was analyzed using descriptive-quantitative. The development of evacuation route, both evacuation line towards temporary evacuation site and evacuation line towads final evacuation site, was conducted by considering road safety, road width, and road accessibility. The study shows that 41% of households were in very high vulnerable condition (level 3) and 51% of households were on the vulnerability level 2. Unfortunately, the high level of community vulnerability was not anticipated by a good community capacity. This was demonstrated by 43% (157) of households at very low level capacity (level 3). Barrier of evacuation due to the road condition (narrow streets <1.5 m, old and fragile buildings/walls around the street, as well as the limited availability of open space) results in some households in RT 4 and RT 3 having difficulty in evacuation.